Durable concrete and preparation method thereof

By combining three-dimensional fiber structure mesh with hybrid fillers in concrete, the problem of cracks and strength reduction in concrete during long-term use is solved, and high-strength crack resistance and durability improvement is achieved.

CN119613021AInactive Publication Date: 2025-03-14QUANZHOU FUYANG STONE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411518163.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing concrete is prone to cracks and strength reduction in long-term use, mainly due to uneven deformation caused by shrinkage and thermal expansion and loss of calcium hydroxide caused by contact with water.

Method used

The durable concrete preparation method with a three-dimensional fiber structure web combined with a hybrid filler is adopted to form a three-dimensional fiber structure web by reacting a mannich with a mannich of aminated mesoporous silica fiber with hydroxypropyl methyl cellulose, and hybrid filler is prepared by a combination of modified graphene and octaaminopropyl cage polysilsesquioxane to enhance the hydrophobic, cracking resistance and durability of the concrete.

Benefits of technology

The high-strength anti-cracking effect of concrete is achieved, reducing the internal erosion by external factors, significantly improving the durability of concrete, and minimizing its wear during long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107290720000081
    Figure BDA0005107290720000081
  • Figure BDA0005107290720000091
    Figure BDA0005107290720000091
Patent Text Reader

Abstract

The invention discloses durable concrete and a preparation method thereof, and relates to the technical field of concrete. According to the invention, mesoporous silica fibers are modified, the surfaces of the mesoporous silica fibers are aminated, and then amino groups on the mesoporous silica fibers and methoxyl groups on hydroxypropyl methyl cellulose are subjected to Mannich reaction chemical bonding to form a three-dimensional fiber structure net, so that the performance strength of the concrete is enhanced, slow loss of water is ensured, and the thermal expansion coefficient of the concrete is reduced; the high-strength anti-cracking effect of the concrete is achieved, so that the concrete is very durable; secondly, carboxyl of modified graphene and aminopropyl of octa-aminopropyl polyhedral oligomeric silsesquioxane are reacted and combined to prepare a hybrid filler, so that the dispersity of graphene is solved, various properties of the concrete are enhanced, the graphene interacts with a three-dimensional fiber structure net, the hydrophobic effect is achieved, meanwhile, the wear resistance of the concrete can be improved, and the service life of the concrete is prolonged. Therefore, the effect of longer service time is achieved. The concrete prepared by the invention has the effects of hydrophobicity, cracking resistance and high durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, in particular to a durable concrete and a preparation method thereof. Background Art

[0002] The most common cracks in concrete are caused by shrinkage and thermal expansion. Among the types of concrete shrinkage, plastic shrinkage and dry shrinkage are the main causes of concrete volume deformation. After the concrete hardens, as the surface moisture gradually evaporates, the humidity gradually decreases, and the concrete volume decreases. Because the surface moisture of concrete loses quickly and the internal moisture loses slowly, uneven shrinkage occurs with large surface shrinkage and small internal shrinkage, and cracks are prone to appear on the concrete surface.

[0003] Moreover, because concrete needs to be in contact with rainwater, distilled water, river and lake water with low bicarbonate content for a long time, the concentration of calcium hydroxide in cement is easily lost under the action of water flow and water pressure. As the concentration of calcium hydroxide continues to decrease, concrete is easily corroded, which reduces the strength of concrete and easily affects the durability of concrete, thus falling into a vicious circle. Therefore, how to improve the durability of concrete is a technical problem that needs to be solved urgently. Summary of the invention

[0004] The object of the present invention is to provide a durable concrete and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a durable concrete, wherein the concrete is a durable concrete modified by combining a three-dimensional fiber structure network with a hybrid filler.

[0006] Furthermore, the three-dimensional fiber structure network is formed by modifying amino-modified mesoporous silica fibers and chemically combining the amino groups on the fibers with the methoxy groups on the hydroxypropyl methylcellulose through a Mannich reaction.

[0007] Furthermore, the hybrid filler is prepared from modified graphene inorganic matter and octaaminopropyl cage-type polysilsesquioxane organic matter.

[0008] Furthermore, a method for preparing durable concrete comprises the following preparation steps:

[0009] (1) 0.8-1.2 parts of hexadecyltrimethylammonium bromide are dissolved in a mixed solution consisting of 6-7 parts of ethanol / water, and the mixture is stirred at 300 rpm for 10-20 minutes at 45°C; then 0.3-0.5 parts of 3-aminopropyltriethoxysilane are slowly added dropwise thereto, and the mixture is stirred at 300 rpm for 30 minutes; after the stirring is completed, 1-1.4 parts of a hydrochloric acid aqueous solution are slowly added dropwise, and then 3.5-4.5 parts of ethyl orthosilicate are slowly added dropwise, and finally 0.1 parts of a hydrochloric acid aqueous solution is slowly added dropwise, and then the mixture is stirred at 45°C at 150 rpm for 30 minutes to prepare a The oligomer solution was obtained; the temperature was raised to 60°C, 4 parts of polyvinyl alcohol aqueous solution were slowly added dropwise into the oligomer solution, and the stirring was continued at 150 rpm for 1 hour to obtain a spinning solution; the spinning solution was allowed to stand for 1.5 hours, and then extracted with a micro syringe, and the spinning parameters were adjusted, the voltage was 10-12 kV, and the injection rate was 0.5 mL / h; the fiber was deposited on the substrate for 2 hours, and then the fiber membrane on the substrate was removed, dried at 80°C for 12 hours, and then placed in a Soxhlet extractor, ethanol was used as an extractant, and the extraction was carried out for 24 hours to remove the template agent hexadecyltrimethylammonium bromide, and amino-modified mesoporous silica fibers were obtained;

[0010] (2) 0.5-2.5 parts of graphene powder and 7-11 parts of ferrous oxalate were placed in a corundum ball mill and ball milled for 1 hour at a ball milling speed of 300 rpm. The medium was zirconium dioxide balls with a diameter of 8 mm and a ball-to-material ratio of 1:12. 40-50 parts of potassium persulfate were added to the corundum ball mill and the ball milling was continued for 2 hours. Subsequently, 500 parts of deionized water were added and the ball milling was continued for 2 hours. After the ball milling was completed, the liquid in the ball mill was sieved and filtered, and the filter cake was retained and washed twice with a hydrochloric acid aqueous solution, then washed twice with a disodium ethylenediaminetetraacetic acid aqueous solution, and finally washed twice with deionized water. , dried at 50°C for 5h to obtain carboxylated graphene powder; 5 to 20 parts of carboxylated graphene powder were added to 1000 parts of ethyl acetate and ultrasonicated for 20 to 30 min, with an ultrasonic power of 35kHz, and then octaaminopropyl cage-type polysilsesquioxane and 0.01 times the weight of N-hydroxysuccinimide and 0.6 times the weight of maleic anhydride were added, and the mixture was stirred at 60°C and 300rpm for 2 to 4h, filtered, and the filtrate was removed. The filtered solid was washed with anhydrous ethanol for 5 times, and dried in a 0.085MPa vacuum oven to constant weight to obtain a hybrid filler;

[0011] (3) Cement, water, hydroxypropyl methylcellulose, amino-modified mesoporous silica fiber, crushed stone and fine sand are first stirred at a speed of 100 rpm for 10 to 30 minutes to form a premixed mixture, and then fly ash and hybrid filler are added and stirred for 10 to 30 minutes to prepare a concrete mixture. The concrete mixture is immediately poured into the formwork and kept at 27°C for 28 days for static curing. After molding and demolding, durable concrete is obtained.

[0012] Furthermore, in the ethanol / water mixed solution in step (1), ethanol accounts for 55% by weight and water accounts for 45% by weight.

[0013] Furthermore, the concentration of the aqueous hydrochloric acid solution in step (1) is 2 mol / L.

[0014] Furthermore, the concentration of the polyvinyl alcohol aqueous solution in step (1) is 10 wt %.

[0015] Furthermore, the concentration of the aqueous hydrochloric acid solution in step (2) is 3%.

[0016] Furthermore, the concentration of the disodium ethylenediaminetetraacetic acid aqueous solution in step (2) is 0.5%.

[0017] Furthermore, the concrete in step (3) comprises, by weight, 300 parts of cement; 150 parts of water; 30 parts of fly ash; 10-20 parts of hybrid filler; 1000 parts of crushed stone; 700 parts of fine sand; 8-12 parts of hydroxypropyl methylcellulose; 12-20 parts of amino-modified mesoporous silica fibers; and 10 parts of paraffin particles.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The present invention prepares concrete with a three-dimensional fiber structure network combined with a hybrid filler to achieve the effects of water repellency, crack resistance and high durability.

[0020] First, the mesoporous silica fiber is modified to make its surface amino, and then the amino group on it is chemically combined with the methoxy group on the hydroxypropyl methylcellulose by Mannich reaction. After the two different types and sizes of fibers are combined in the concrete, a three-dimensional fiber structure network is formed. On the one hand, the strong combination further enhances the performance strength of the concrete. On the other hand, the hydroxypropyl methylcellulose acts as a water retaining agent to ensure the slow loss of water to avoid cracking caused by excessive loss of water. The mesoporous silica fiber reduces the thermal expansion coefficient of the concrete. The combination of the two reduces the shrinkage or expansion of the concrete. In summary, the concrete achieves a high-strength and anti-cracking effect, thereby reducing the erosion of the internal factors by external factors, making it very durable.

[0021] Secondly, hybrid fillers are prepared by combining modified graphene inorganic matter with octaaminopropyl cage-type polysilsesquioxane organic matter. The surface of the modified graphene is rich in carboxyl groups, which are firmly combined with the aminopropyl groups on the eight corners of the cage-type hexahedron of octaaminopropyl cage-type polysilsesquioxane through amidation, thereby solving the problem of graphene dispersibility. The prepared hybrid filler enhances the various properties of concrete, interacts with the three-dimensional fiber structure network, achieves a hydrophobic effect, and can improve the wear resistance of concrete, so that after the concrete is put into use, the wear is minimized, thereby achieving the effect of longer service life. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a durable concrete prepared in the following examples are as follows:

[0024] Anti-penetration test: According to the anti-penetration grade specified in GB 50164 "Concrete Quality Control Standard": The examples and concrete are made into corresponding sizes, cured for 28 days at a temperature of 22°C and a relative humidity of 95%, and the maximum water pressure that can be withstood when tested according to the standard test method is used to measure the anti-penetration pressure.

[0025] Cracking resistance: According to the early cracking resistance test of GB / T50082, the examples and concrete were made into corresponding sizes, cured for 28 days at a temperature of 22°C and a relative humidity of 95%, and the total cracking area per unit area was measured.

[0026] Durability: According to the provisions of GB / T50082-2009 Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete, the examples and concrete were made into corresponding sizes and cured for 28 days at a temperature of 22°C and a relative humidity of 95%. The average carbonation depth of the concrete was measured.

[0027] Example 1

[0028] (1) 0.8 parts of hexadecyltrimethylammonium bromide was dissolved in a mixed solution consisting of 6 parts of ethanol / water, wherein the ethanol accounted for 55% by mass and the water accounted for 45% by mass, and the mixture was stirred at 300 rpm for 10 min at 45° C.; then 0.3 parts of 3-aminopropyltriethoxysilane was slowly added dropwise thereto, and the mixture was stirred at 300 rpm for 30 min; after the stirring was completed, 1 part of a 2 mol / L hydrochloric acid aqueous solution was slowly added dropwise, and then 3.5 parts of ethyl orthosilicate was slowly added dropwise, and finally 0.1 part of a hydrochloric acid aqueous solution was slowly added dropwise, and then the mixture was stirred at 45° C. and 150 rpm for 30 min. 0min, to obtain an oligomer solution; raise the temperature to 60°C, slowly drop 4 portions of a 10wt% polyvinyl alcohol aqueous solution into the oligomer solution, continue stirring at 150rpm for 1h, to obtain a spinning solution; let the spinning solution stand for 1.5h, then extract it with a micro syringe, adjust the spinning parameters, the voltage is 10kV, and the injection rate is 0.5mL / h; the fiber is deposited on the substrate for 2h, then the fiber membrane on the substrate is removed, dried at 80°C for 12h, then placed in a Soxhlet extractor, using ethanol as an extractant, extracting for 24h, removing the template agent hexadecyltrimethylammonium bromide, to obtain amino mesoporous silica fibers;

[0029] (2) 0.5 parts of graphene powder and 7 parts of ferrous oxalate were placed in a corundum ball mill and ball milled for 1 hour at a ball milling speed of 300 rpm. The medium was zirconium dioxide balls with a diameter of 8 mm and a ball-to-material ratio of 1:12. 40 parts of potassium persulfate were added to the corundum ball mill and the ball milling was continued for 2 hours. Subsequently, 500 parts of deionized water were added and the ball milling was continued for 2 hours. After the ball milling was completed, the liquid in the ball mill was sieved and filtered, and the filter cake was retained and washed twice with a 3% hydrochloric acid aqueous solution, and then washed twice with a 0.5% disodium ethylenediaminetetraacetic acid aqueous solution, and finally washed with a deionized water solution. The obtained product was washed twice with water and dried at 50°C for 5 hours to obtain carboxylated graphene powder; 5 parts of carboxylated graphene powder were added to 1000 parts of ethyl acetate and ultrasonicated for 20 minutes at an ultrasonic power of 35kHz, and then octaaminopropyl cage-type polysilsesquioxane and 0.01 times the weight of N-hydroxysuccinimide and 0.6 times the weight of maleic anhydride were added, and the mixture was stirred at 60°C and 300rpm for 2 hours, filtered, and the filtrate was removed. The filtered solid was washed with anhydrous ethanol for 5 times, and dried in a 0.085MPa vacuum oven to constant weight to obtain a hybrid filler;

[0030] (3) Composition of concrete by weight: 300 parts of cement; 150 parts of water; 30 parts of fly ash; 10 parts of hybrid filler; 1000 parts of crushed stone; 700 parts of fine sand; 8 parts of hydroxypropyl methylcellulose; 12 parts of amino-modified mesoporous silica fiber; 10 parts of paraffin particles; first, the cement, water, hydroxypropyl methylcellulose, amino-modified mesoporous silica fiber, crushed stone and fine sand were stirred at a speed of 100 rpm for 10 minutes to form a premixed mixture, and then fly ash and hybrid filler were added and stirred for 10 minutes to prepare a concrete mixture. The concrete mixture was immediately poured into the formwork and kept at 27°C for 28 days for curing. After molding and demolding, durable concrete was obtained.

[0031] Example 2

[0032] (1) Dissolve 1 part of hexadecyltrimethylammonium bromide in a mixed solution consisting of 6.5 parts of ethanol / water, wherein the ethanol accounts for 55% by mass and the water accounts for 45% by mass, and stir at 300 rpm for 15 min at 45° C.; then slowly drop 0.4 parts of 3-aminopropyltriethoxysilane therein, and continue stirring at 300 rpm for 30 min; after the stirring is completed, slowly drop 1.2 parts of a 2 mol / L hydrochloric acid aqueous solution, then slowly drop 4 parts of ethyl orthosilicate, and finally slowly drop 0.1 parts of a hydrochloric acid aqueous solution, and then stir at 45° C. and 150 rpm for 3 0min, to obtain an oligomer solution; raise the temperature to 60°C, slowly drop 4 portions of a 10wt% polyvinyl alcohol aqueous solution into the oligomer solution, continue stirring at 150rpm for 1h, to obtain a spinning solution; let the spinning solution stand for 1.5h, then extract it with a micro syringe, adjust the spinning parameters, the voltage is 11kV, and the injection rate is 0.5mL / h; the fiber is deposited on the substrate for 2h, then the fiber membrane on the substrate is removed, dried at 80°C for 12h, then placed in a Soxhlet extractor, using ethanol as an extractant, extracting for 24h, removing the template agent hexadecyltrimethylammonium bromide, to obtain amino mesoporous silica fibers;

[0033] (2) 1.5 parts of graphene powder and 9 parts of ferrous oxalate were placed in a corundum ball mill and ball milled for 1 hour at a ball milling speed of 300 rpm. The medium was zirconium dioxide balls with a diameter of 8 mm and a ball-to-material ratio of 1:12. 45 parts of potassium persulfate were added to the above corundum ball mill and the ball milling was continued for 2 hours. Subsequently, 500 parts of deionized water were added and the ball milling was continued for 2 hours. After the ball milling was completed, the liquid in the ball mill was sieved and filtered, and the filter cake was retained and washed twice with a 3% hydrochloric acid aqueous solution, and then washed twice with a 0.5% disodium ethylenediaminetetraacetic acid aqueous solution, and finally washed with deionized water. Wash twice, dry at 50°C for 5h to obtain carboxylated graphene powder; add 12.5 parts of carboxylated graphene powder to 1000 parts of ethyl acetate and ultrasonicate for 25min, the ultrasonic power is 35kHz, then add octaaminopropyl cage-type polysilsesquioxane and 0.01 times the weight of N-hydroxysuccinimide and 0.6 times the weight of maleic anhydride, stir at 60°C and 300rpm, react for 3h, filter, remove the filtrate, filter out the solid, wash it with anhydrous ethanol 5 times, and dry it in a 0.085MPa vacuum oven to constant weight to obtain a hybrid filler;

[0034] (3) Composition of concrete by weight: 300 parts of cement; 150 parts of water; 30 parts of fly ash; 15 parts of hybrid filler; 1000 parts of crushed stone; 700 parts of fine sand; 10 parts of hydroxypropyl methylcellulose; 16 parts of amino-modified mesoporous silica fiber; 10 parts of paraffin particles; first, the cement, water, hydroxypropyl methylcellulose, amino-modified mesoporous silica fiber, crushed stone and fine sand were stirred at a speed of 100 rpm for 20 minutes to form a premixed mixture, and then fly ash and hybrid filler were added and stirred for 20 minutes to prepare a concrete mixture. The concrete mixture was immediately poured into the formwork and kept at 27°C for 28 days for curing. After molding and demolding, durable concrete was obtained.

[0035] Example 3

[0036] (1) 1.2 parts of hexadecyltrimethylammonium bromide were dissolved in a mixed solution consisting of 7 parts of ethanol / water, wherein the ethanol accounted for 55% by mass and the water accounted for 45% by mass, and the mixture was stirred at 300 rpm for 20 min at 45° C.; then 0.5 parts of 3-aminopropyltriethoxysilane were slowly added dropwise thereto, and the mixture was stirred at 300 rpm for 30 min; after the stirring was completed, 1.4 parts of a 2 mol / L hydrochloric acid aqueous solution were slowly added dropwise, and then 4.5 parts of ethyl orthosilicate were slowly added dropwise, and finally 0.1 parts of a hydrochloric acid aqueous solution were slowly added dropwise, and then the mixture was stirred at 150 rpm at 45° C. 30min to obtain an oligomer solution; raise the temperature to 60°C, slowly add 4 parts of a 10wt% polyvinyl alcohol aqueous solution into the oligomer solution, and continue stirring at 150rpm for 1h to obtain a spinning solution; let the spinning solution stand for 1.5h, then extract it with a micro syringe, adjust the spinning parameters, the voltage is 12kV, and the injection rate is 0.5mL / h; the fiber is deposited on the substrate for 2h, then the fiber membrane on the substrate is removed, dried at 80°C for 12h, and then placed in a Soxhlet extractor, using ethanol as an extractant, extracting for 24h, removing the template agent hexadecyltrimethylammonium bromide, and obtaining amino mesoporous silica fibers;

[0037] (2) 2.5 parts of graphene powder and 11 parts of ferrous oxalate were placed in a corundum ball mill and ball milled for 1 hour at a ball milling speed of 300 rpm. The medium was zirconium dioxide balls with a diameter of 8 mm and a ball-to-material ratio of 1:12. 50 parts of potassium persulfate were added to the corundum ball mill and the ball milling was continued for 2 hours. Subsequently, 500 parts of deionized water were added and the ball milling was continued for 2 hours. After the ball milling was completed, the liquid in the ball mill was sieved and filtered, and the filter cake was retained and washed twice with a 3% hydrochloric acid aqueous solution, and then washed twice with a 0.5% disodium ethylenediaminetetraacetic acid aqueous solution, and finally washed with a deionized water solution. The obtained product was washed twice with water and dried at 50°C for 5 hours to obtain carboxylated graphene powder; 20 parts of carboxylated graphene powder were added to 1000 parts of ethyl acetate and ultrasonicated for 30 minutes at an ultrasonic power of 35kHz, and then octaaminopropyl cage-type polysilsesquioxane and 0.01 times the weight of N-hydroxysuccinimide and 0.6 times the weight of maleic anhydride were added, and the mixture was stirred at 60°C and 300rpm for 4 hours, filtered, and the filtrate was removed. The filtered solid was washed with anhydrous ethanol for 5 times, and dried in a 0.085MPa vacuum oven to constant weight to obtain a hybrid filler;

[0038] (3) Composition of concrete by weight: 300 parts of cement; 150 parts of water; 30 parts of fly ash; 20 parts of hybrid filler; 1000 parts of crushed stone; 700 parts of fine sand; 12 parts of hydroxypropyl methylcellulose; 20 parts of amino-modified mesoporous silica fiber; 10 parts of paraffin particles; first, the cement, water, hydroxypropyl methylcellulose, amino-modified mesoporous silica fiber, crushed stone and fine sand were stirred at a speed of 100 rpm for 30 minutes to form a premixed mixture, and then fly ash and hybrid filler were added and stirred for 30 minutes to prepare a concrete mixture. The concrete mixture was immediately poured into the formwork and kept at 27°C for 28 days for curing. After molding and demolding, durable concrete was obtained.

[0039] Comparative Example 1

[0040] The difference between Comparative Example 1 and Example 2 is that step (1) is different, and step (3) is changed to: dissolving 1 part of hexadecyltrimethylammonium bromide in a mixed solution consisting of 6.5 parts of ethanol / water, wherein the ethanol accounts for 55% by mass and the water accounts for 45% by mass, and stirring at 300 rpm for 15 min at 45° C.; then slowly adding 1.2 parts of a 2 mol / L hydrochloric acid aqueous solution thereto, then slowly adding 4 parts of tetraethyl orthosilicate, and finally slowly adding 0.1 parts of a hydrochloric acid aqueous solution, and then stirring at 150 rpm for 30 min at 45° C. to obtain an oligomer solution; The temperature was raised to 60°C, and 4 portions of 10 wt% polyvinyl alcohol aqueous solution were slowly dripped into the oligomer solution, and stirring was continued at 150 rpm for 1 hour to obtain a spinning solution; the spinning solution was allowed to stand for 1.5 hours, and then extracted with a microsyringe, and the spinning parameters were adjusted to a voltage of 11 kV and an injection rate of 0.5 mL / h; the fiber was deposited on the substrate for 2 hours, and then the fiber membrane on the substrate was removed, dried at 80°C for 12 hours, and then placed in a Soxhlet extractor, using ethanol as an extractant, and extracted for 24 hours to remove the template agent hexadecyltrimethylammonium bromide to obtain amino-modified mesoporous silica fibers; the remaining steps were the same as those in Example 2.

[0041] Comparative Example 2

[0042] The difference between Comparative Example 2 and Example 2 is that step (1) is omitted, and step (3) is changed to: concrete composition by weight: 300 parts of cement; 150 parts of water; 30 parts of fly ash; 15 parts of hybrid filler; 1000 parts of crushed stone; 700 parts of fine sand; 10 parts of hydroxypropyl methylcellulose; 10 parts of paraffin particles; first, cement, water, hydroxypropyl methylcellulose, crushed stone and fine sand are stirred at a speed of 100 rpm for 20 minutes to form a premixed mixture, and then fly ash and hybrid filler are added and stirred for 20 minutes to obtain a concrete mixture, which is immediately poured into the template and kept at 27°C for 28 days. After molding and demolding, durable concrete is obtained; the remaining steps are the same as in Example 2.

[0043] Comparative Example 3

[0044] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: 12.5 parts of graphene powder are added to 1000 parts of ethyl acetate and ultrasonicated for 25 minutes, the ultrasonic power is 35kHz, and then octaaminopropyl cage-type polysilsesquioxane and octaaminopropyl cage-type polysilsesquioxane are added. 0.01 times the weight of N-hydroxysuccinimide and 0.6 times the weight of maleic anhydride are added, and the reaction is carried out at 60° C. and 300 rpm under stirring for 3 hours, filtered, and the filtrate is removed. The filtered solid is washed with anhydrous ethanol 5 times, and dried in a 0.085 MPa vacuum oven to constant weight to obtain a hybrid filler; the remaining steps are the same as in Example 2.

[0045] Comparative Example 4

[0046] The difference between Comparative Example 4 and Example 2 lies in the difference in steps (2) (3), where steps (2) (3) are modified as follows: (2) 1.5 parts of graphene powder and 9 parts of ferrous oxalate are placed in a corundum ball mill and ball milled for 1 h at a ball milling speed of 300 rpm, using zirconium dioxide balls with a diameter of 8 mm and a ball-to-material ratio of 1:12; 45 parts of potassium persulfate are added to the corundum ball mill and ball milling is continued for 2 h, followed by addition of 500 parts of deionized water and ball milling for 2 h; after the ball milling is completed, the liquid in the ball mill is sieved and filtered, the filter cake is retained, and washed twice with a 3% aqueous hydrochloric acid solution, then washed twice with a 0.5% aqueous disodium ethylenediaminetetraacetic acid solution, and finally washed twice with deionized water, and dried at 50° C. for 5 h to obtain carboxylated graphene powder;

[0047] (3) Concrete composition by weight: 300 parts of cement; 150 parts of water; 30 parts of fly ash; 15 parts of carboxylated graphene powder; 1000 parts of crushed stone; 700 parts of fine sand; 10 parts of hydroxypropyl methylcellulose; 16 parts of amino-modified mesoporous silica fiber; 10 parts of paraffin particles; first, the cement, water, hydroxypropyl methylcellulose, amino-modified mesoporous silica fiber, crushed stone and fine sand were stirred at a speed of 100 rpm for 20 minutes to form a premixed mixture, and then fly ash and carboxylated graphene powder were added and stirred for 20 minutes to prepare a concrete mixture. The concrete mixture was immediately poured into the formwork and kept at 27°C for 28 days. After molding and demolding, durable concrete was obtained; the remaining steps were the same as in Example 2.

[0048] Comparative Example 5

[0049] The difference between Comparative Example 5 and Example 2 is that there is no step (2), and step (3) is changed to: concrete composition by weight: 300 parts of cement; 150 parts of water; 30 parts of fly ash; 15 parts of octaaminopropyl cage-type polysilsesquioxane; 1000 parts of crushed stone; 700 parts of fine sand; 10 parts of hydroxypropyl methylcellulose; 16 parts of amino-modified mesoporous silica fiber; 10 parts of paraffin particles; first, the cement, water, hydroxypropyl methylcellulose, amino-modified mesoporous silica fiber, crushed stone and fine sand are stirred at a speed of 100 rpm for 20 minutes to form a premixed mixture, and then fly ash and octaaminopropyl cage-type polysilsesquioxane are added, and stirring is continued for 20 minutes to obtain a concrete mixture, and the concrete mixture is immediately poured into the template, kept at 27°C for 28 days, and after molding and demolding, a durable concrete is obtained; the remaining steps are the same as in Example 2.

[0050] Effect example

[0051] Table 1 below shows the performance analysis results of a durable concrete using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0052] Table 1

[0053]

[0054]

[0055] From the comparison of the experimental data of crack resistance and durability of the embodiment and the comparative example, it can be found that the present invention modifies the mesoporous silica fiber, makes its surface amino, and then the amino group on it and the methoxy group on the hydroxypropyl methylcellulose undergo Mannich reaction chemical combination, and the two fibers of different types and sizes are combined in the concrete to form a three-dimensional fiber structure network. On the one hand, the strong combination further enhances the performance strength of the concrete, and on the other hand, the hydroxypropyl methylcellulose acts as a water retaining agent to ensure the slow loss of water to avoid cracking caused by excessive loss of water, and the mesoporous silica fiber reduces the thermal expansion coefficient of the concrete. The combination of the two reduces the shrinkage or expansion of the concrete. In summary, the concrete achieves a high-strength anti-cracking effect, thereby reducing External factors can resist internal erosion, so it is very durable; from the comparison of the experimental data of hydrophobicity and durability of the embodiment and the comparative example, it can be found that the present invention prepares a hybrid filler by using modified graphene inorganic matter and octaaminopropyl cage-type polysilsesquioxane organic matter, and the surface of the modified graphene is rich in carboxyl groups, which are firmly combined with the aminopropyl groups on the eight corners of the cage-type hexahedron of octaaminopropyl cage-type polysilsesquioxane through amidation, thereby solving the problem of graphene dispersibility. The prepared hybrid filler enhances the various properties of concrete, interacts with the three-dimensional fiber structure network, achieves a hydrophobic effect, and can improve the wear resistance of concrete, so that after the concrete is put into use, the wear is minimized, thereby achieving the effect of longer service life.

[0056] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A durable concrete, characterized in that: The concrete is a durable concrete modified by combining a three-dimensional fiber structure network with a hybrid filler.

2. The durable concrete according to claim 1, characterized in that: The three-dimensional fiber structure net is formed by modifying amino-modified mesoporous silica fiber and chemically combining the amino groups on the fiber with the methoxy groups on the hydroxypropyl methylcellulose through Mannich reaction.

3. The durable concrete according to claim 1, characterized in that: The hybrid filler is prepared from modified graphene inorganic matter and octaaminopropyl cage-type polysilsesquioxane organic matter.

4. A method for preparing durable concrete, characterized in that: The method comprises the following preparation steps: (1) 0.8-1.2 parts of hexadecyltrimethylammonium bromide are dissolved in a mixed solution consisting of 6-7 parts of ethanol / water, and the mixture is stirred at 300 rpm for 10-20 minutes at 45°C; then 0.3-0.5 parts of 3-aminopropyltriethoxysilane are slowly added dropwise thereto, and the mixture is stirred at 300 rpm for 30 minutes; after the stirring is completed, 1-1.4 parts of a hydrochloric acid aqueous solution are slowly added dropwise, and then 3.5-4.5 parts of ethyl orthosilicate are slowly added dropwise, and finally 0.1 parts of a hydrochloric acid aqueous solution is slowly added dropwise, and then the mixture is stirred at 45°C at 150 rpm for 30 minutes to prepare a The oligomer solution was obtained; the temperature was raised to 60°C, 4 parts of polyvinyl alcohol aqueous solution were slowly added dropwise into the oligomer solution, and the stirring was continued at 150 rpm for 1 hour to obtain a spinning solution; the spinning solution was allowed to stand for 1.5 hours, and then extracted with a micro syringe, and the spinning parameters were adjusted, the voltage was 10-12 kV, and the injection rate was 0.5 mL / h; the fiber was deposited on the substrate for 2 hours, and then the fiber membrane on the substrate was removed, dried at 80°C for 12 hours, and then placed in a Soxhlet extractor, ethanol was used as an extractant, and the extraction was carried out for 24 hours to remove the template agent hexadecyltrimethylammonium bromide, and amino-modified mesoporous silica fibers were obtained; (2) 0.5-2.5 parts of graphene powder and 7-11 parts of ferrous oxalate were placed in a corundum ball mill and ball milled for 1 hour at a ball milling speed of 300 rpm. The medium was zirconium dioxide balls with a diameter of 8 mm and a ball-to-material ratio of 1:

12. 40-50 parts of potassium persulfate were added to the corundum ball mill and the ball milling was continued for 2 hours. Subsequently, 500 parts of deionized water were added and the ball milling was continued for 2 hours. After the ball milling was completed, the liquid in the ball mill was sieved and filtered, and the filter cake was retained and washed twice with a hydrochloric acid aqueous solution, then washed twice with a disodium ethylenediaminetetraacetic acid aqueous solution, and finally washed twice with deionized water. , dried at 50°C for 5h to obtain carboxylated graphene powder; 5 to 20 parts of carboxylated graphene powder were added to 1000 parts of ethyl acetate and ultrasonicated for 20 to 30 min, with an ultrasonic power of 35kHz, and then octaaminopropyl cage-type polysilsesquioxane and 0.01 times the weight of N-hydroxysuccinimide and 0.6 times the weight of maleic anhydride were added, and the mixture was stirred at 60°C and 300rpm for 2 to 4h, filtered, and the filtrate was removed. The filtered solid was washed with anhydrous ethanol for 5 times, and dried in a 0.085MPa vacuum oven to constant weight to obtain a hybrid filler; (3) Cement, water, hydroxypropyl methylcellulose, amino-modified mesoporous silica fiber, crushed stone and fine sand are first stirred at a speed of 100 rpm for 10 to 30 minutes to form a premixed mixture, and then fly ash and hybrid filler are added and stirred for 10 to 30 minutes to prepare a concrete mixture. The concrete mixture is immediately poured into the formwork and kept at 27°C for 28 days for static curing. After molding and demolding, durable concrete is obtained.

5. The method for preparing durable concrete according to claim 4, characterized in that: In the ethanol / water mixed solution in step (1), ethanol accounts for 55% by weight, and water accounts for 45% by weight.

6. The method for preparing durable concrete according to claim 4, characterized in that: The concentration of the hydrochloric acid aqueous solution in step (1) is 2 mol / L.

7. The method for preparing durable concrete according to claim 4, characterized in that: The concentration of the polyvinyl alcohol aqueous solution in step (1) is 10 wt %.

8. The method for preparing durable concrete according to claim 4, characterized in that: The concentration of the hydrochloric acid aqueous solution in step (2) is 3%.

9. The method for preparing durable concrete according to claim 4, characterized in that: The concentration of the disodium ethylenediaminetetraacetic acid aqueous solution in step (2) is 0.5%.

10. The method for preparing durable concrete according to claim 4, characterized in that: The concrete composition in step (3) is as follows: 300 parts by weight of cement; 150 parts by weight of water; 30 parts by weight of fly ash; 10 to 20 parts by weight of hybrid filler; 1,000 parts by weight of crushed stone; 700 parts by weight of fine sand; 8 to 12 parts by weight of hydroxypropyl methylcellulose; 12 to 20 parts by weight of amino-modified mesoporous silica fibers; and 10 parts by weight of paraffin particles.